If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 0 + b Remove the zero: -3 = b Solving -3 = b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -3 + -1b = b + -1b Combine like terms: b + -1b = 0 -3 + -1b = 0 Add '3' to each side of the equation. -3 + 3 + -1b = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1b = 0 + 3 -1b = 0 + 3 Combine like terms: 0 + 3 = 3 -1b = 3 Divide each side by '-1'. b = -3 Simplifying b = -3
| 7d-4d+d+6=6d | | 5.3x=-12 | | Log[5](3X-11)=2 | | 0.7=(580000-x)/580000 | | 4(4x-1)-7x=3/8 | | 12k-k-20=0 | | X+9+2x+8=-4 | | (3.6y+1)/.4=3.3y | | 3(2+5)=2+19 | | (3.6y+1)/04=3.3y | | m+20=80 | | Y^4=400 | | 7x^6=12 | | -2/4/7 | | 2r-36=6r-12 | | 0=4k^2-15k+20 | | -35/-0.875 | | 3(k+1)+2k=13 | | 2x^4=120 | | -7x^2-24x-9=0 | | 3m+4=12 | | p14=-20 | | m+80=140 | | t(25)=0.07(25)^3/2 | | 6x=-18y-12 | | 5x-3=6x-2x | | 0y-5(1+y)=3(2y-2)-20 | | F(x)=(t-1)(t+3) | | 2t-7-52=11 | | 3x-5=7x-49 | | 42=-6g | | 4/9y-3 |